Deformation analysis of reinforced‐core auxetic assemblies by close‐range photogrammetry. Issue 7 (15th June 2016) - Shufrin, Igor; Pasternak, Elena; Dyskin, Arcady V.
Abstract : In this article, we present an experimental study validating the concept of the reinforced‐core auxetic assemblies. The main distinctive feature of these assemblies is the presence of a reinforcing core in the microstructural units that increases the shear stiffness and thus produces negative Poisson's ratio. We tested a number of prototypes manufactured using the stereolithography and selective laser sintering methods. To measure the deformations, we employed the close‐range photogrammetry method, which enables monitoring of locations of unlimited number of points from digital images. We developed a procedure for multi‐point measurement of planar deformations using a single digital camera. This procedure allows for continuous measurement of deformations without interruption to the loading sequence. Camera self‐calibration is based on multiple images of stable reference points, which enables high accuracy of the measurements even using a consumer grade digital camera. We compare the obtained experimental results with a simplified continuum model. We demonstrate a good agreement between the theoretical predictions and the experimental results.